The effectiveness of subsidies revisited: Accounting for wage and employment effects in business R&D - Volker Reinthaler; Guntram B. Wolff (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2004)
The present paper investigates the effectiveness of public subsidies to business enterprise research in a panel of OECD countries. We contribute to the literature by explicitly distinguishing between effects of a subsidy on R&D employment and expenditure, thereby accounting for a potential increase in scientists' wages. The results indicate that subsidies are effective in generating additional research. We find that an increase in the direct subsidy rate of one percentage point leads to at least 1% more business R&D employment in the long run. Expenditure for business research increases by roughly 20-30% more than employment. We take this as evidence that subsidies also raise scientists' wages. In addition, we find that there exists significant crowding out of private research through university research. Research performed in public non-university institutions seems to have no effect on private research.
Keywords: 330